2012
DOI: 10.4236/health.2012.42012
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study on delay in treatment initiation of cancer patients

Abstract: Early diagnosis and timely initiation of treatment of cancer patients may improve survival and quality of life. Various measures of delay can be made during diagnosis and treatment initiation. Most of the studies were based on single type of cancer with different definitions and measurements of delay in diagnosis and treatment. Thus, it has been difficult to synthesize results and generalize to other types of cancer. The study proposes to measure total duration between onsets of symptom to start of treatment i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
23
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 35 publications
10
23
2
1
Order By: Relevance
“…The foregoing observation clearly indicated that there was no particular relationship between positive and significant sca effects of crosses with gca effects of their parents for the characters under study. Saleem et al, (2010), Saidaiah et al, (2011);Dwivedi and Pandey (2012); Sanghara and Hussain (2012) and Tiwari et al, (2014) have also reported similar findings. High × high, high × average and average × average crosses give transgressive segregants and selection in early generation would be advantageous for development of pure lines as there are involvement of additive gene action, whereas, crosses having high × low, average × low and low × low general combining parents are suggested for heterosis breeding as their inheritance are controlled by non-additive and epistatic gene action.…”
Section: Specific Combining Ability Effectsupporting
confidence: 70%
“…The foregoing observation clearly indicated that there was no particular relationship between positive and significant sca effects of crosses with gca effects of their parents for the characters under study. Saleem et al, (2010), Saidaiah et al, (2011);Dwivedi and Pandey (2012); Sanghara and Hussain (2012) and Tiwari et al, (2014) have also reported similar findings. High × high, high × average and average × average crosses give transgressive segregants and selection in early generation would be advantageous for development of pure lines as there are involvement of additive gene action, whereas, crosses having high × low, average × low and low × low general combining parents are suggested for heterosis breeding as their inheritance are controlled by non-additive and epistatic gene action.…”
Section: Specific Combining Ability Effectsupporting
confidence: 70%
“…Among them, the clinician delay belongs to secondary delay and tertiary delay. Delay in any phase or no treatment would cause cancer progression to advanced stages, and significantly affects the treatment outcome [ 44 , 45 ]. Phases and characteristics of delay or refusal of therapy are different among different cancers and stages.…”
Section: Discussionmentioning
confidence: 99%
“…Phases and characteristics of delay or refusal of therapy are different among different cancers and stages. For breast cancer, the major type of delay or no treatment was tertiary delay, and followed by primary delay[ 45 ]. Furthermore, phases of therapy delay also depend on region and country (cancer care system), patient characteristics, age as well as cancer staging.…”
Section: Discussionmentioning
confidence: 99%
“…The main reason for primary delay in seeking treatment for oral cancers in Indian population was due to patients themselves (Joshi et al, 2014). Delays have been outlined by Dwivedi et al (2012). Primary delay is defined as the time from the onset of symptoms to first contact with medical persons, secondary delay is defined as the time from contacting the first medical per-son to a confirmed diagnosis and tertiary delay is defined as the time from…”
Section: Introductionmentioning
confidence: 99%